CRITICAL ANALYSIS OF INVESTMENT DECISION IN GOLD AND SILVER DURING THE DIWALI FESTIVAL FOR MULTI COMMODITY EXCHANGE INVESTORS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
An Empirical Analysis has been conducted  to compare and contrast the returns of Gold  Commodity with the silver commodity during  the Diwali Festival. Gold Mini and Silver  Mini have been considered as a base and data  pertaining to 10 years from 2010 to 2019  have been extracted from Multi Commodity  Exchange. Statistical tools have been employed like Karl  Pearson coefficient correlation, the test of  significance of correlation, percentile, and trends  have been utilized to evaluate the impact of the  Diwali festival. The study concludes that Gold  commodity and Silver commodity have a linear  positive relationship corresponding with the  Diwali festival. Considering returns the Gold  commodity is a notch ahead and offers better  returns than the silver commodities. Hence  investors should capitalize on this opportunity  present in Multi commodity exchange.
Keywords: Gold Commodity; Silver commodity; Multi commodity Exchange; Diwali Festival